Malaysian oral health literacy training package @ Celik Literasi Kesihatan Mulut Malaysia (CeLiK-M).module 3: written and Audio Visual Aids (AVA) for Oral Health Education (OHE) - Rani, Haslina; Che Musa, Muhd Firdaus; Zabha, Azliza; Ruslan, Ruzawani; Mohd Jeffry, Sabrina Julia; Abdul Manab, Enny Esdayantey; Kamarozaman, Dewi Mayang Sari (Oral Health Programme, Ministry of Health, 2026)
This module is part of a training package that has been carefully designed as a trainer’s resource to strengthen oral health literacy among oral healthcare personnel in Malaysia. The primary objective of the package is to raise awareness on the importance of oral health literacy and to enhance the essential skills required to address oral health literacy challenges in professional practice. The module emphasises the importance of well-designed written and audiovisual aids in supporting oral health education and literacy. Participants will gain an understanding of how written and audiovisual materials can enhance message clarity, reinforce learning, and support behaviour change when appropriately designed for the target audience. Participants will be guided through techniques on identifying audience needs and characteristics, developing suitable written and audiovisual aids, and selecting formats that are accessible, engaging, and culturally appropriate. Participants will also learn how to review and test educational materials with users to ensure usability, comprehension, and effectiveness, particularly among populations with varying oral health literacy levels.